Study on the Role of Big Data System in Line Loss Lean Management - Wang, Juanjuan; Yao, Bo; Jia, Yujie; Huo, Xuanmin; Liang, Dong; Zhang, Wei; Zhao, Nan (Journal of Theory and Practice of Engineering Science, 2023)
Big data systems play a crucial role in lean management of line losses. By providing real-time data analysis, predictive maintenance, and root cause analysis system functions, they help identify and reduce line losses and optimize performance. The application points of this system include real-time monitoring, root cause analysis, performance optimization, process automation, and continuous improvement.